Extent of Implementing the Principles of Governance in Palestinian Universities and the Relation to their Social Responsibility in Combating Corruption - Mahmoud Abdel Majed Assaf (University of Science and Technology, Yemen, 2018)
The study aimed at identifying the assessment degree given by the faculty members in the Palestinian universities for the extent of implementing principles of governance and the relation between this degree and  their assessment degree of social responsibility in combating corruption. To achieve this objective, the researcher followed the descriptive, analytical method by administering two questionnaires. The first questionnaires included (43) items covering 3 dimensions (accountability and transparency in participation; justice and equality for empowerment; efficiency and effectiveness). The second one consisted of (25) items, describing the social responsibility of universities in the fight against corruption. The sample consisted of (297) faculty members. The results showed that the overall assessment degree of implementing the principles of governance was significant at a relative weight of (75.24%). The dimension of efficiency and effectiveness ranked first with a relative weight of (76.63%. The dimension of accountability and transparency ranked last with a relative weight of (74.51% ), whereas the degree of overall assessment of the members of the sample on the social responsibility of the university in the fight against corruption was significant at a relative weight of (77.11%). There was also a strong positive correlation of a statistical significance of correlation coefficient (0.771) between the faculty members' assessment degree  of the extent of implementing governance principles in Palestinian universities and their assessment degree of the university social responsibility in the fight against corruption. The study recommended the establishment of joint advisory councils consisting of university officials and community leaders to identify and reduce corruption, to activate university's roles in enhancing the values of integrity and transparency by means of services and to supervise various activities. Keywords: Principles of governance, Social responsibility, Corruption.